Effects of intake-port throttling on combustion behaviour in diesel low-temperature combustion. (October 2018) - Sogbesan, Oluwasujibomi; Garner, Colin P; Davy, Martin H
This article describes the effects of intake-port throttling on diesel low-temperature combustion at a low and medium load condition. These conditions were known for their characteristically high hydrocarbon emissions predominantly from over-mixed and under-mixed mixture zones, respectively. The investigation was carried out to supplement current findings in the literature with valuable information on the formation of high hydrocarbon emissions with increasing swirl levels generated by intake-port throttling. This was achieved through the use of cycle-resolved high hydrocarbon measurements in addition to cycle averaged emissions and in-cylinder pressure-derived metrics. While there was negligible overall effect at the moderately dilute low-load conditions, increasing swirl has been shown to be beneficial to premixing efficacy under highly dilute conditions with extended ignition delay. This potential advantage was found to be nullified by the swirl-induced confinement of fuel and combustion products to the central region of the cylinder leading to poor late cycle burn rates and increased smoke emissions. High hydrocarbon emissions from the squish and head quench regions were reduced by an increase in swirl ratio.